PERBEDAAN KINERJA KEUANGAN ANTARA PERUSAHAAN BESAR DAN KECIL YANG MENGUMUMKAN DIVIDEN : PENGUJIAN SIGNALLING HYPOTHESIS - Suhendra, Beni (Jurnal Analisis Bisnis Ekonomi, 2007)
The objectives of this research are to examine a difference of financial performance of large and small-scaled companies that announce the dividend. If there is a difference, is it significant? Total f 30 companies sample have chosen. Analysis performed using independent samples t-test to test the hypothesis. The analysis show for some of the ratios such as current ratio, quich ratio, leverage ratio, return on invesment, return on equity, net profit margin and total assets turnover have no statistically significant result. It means the results that the liquidity performance, the solvability, the profitability and the activity of large and small-called companies that announce the dividend doesn?t differ. This research doesn?s support the signaling hypothesis.